Study on the Quantum Confinement of Photo-Generated Carriers in Quantum Wells - Ding Ding (IEEE Photonics Journal, 2023)
According to the classical theory, multi-quantum wells (MQWs) have quantum confinement effect on photo-generated carriers, which limits its application in light-to-electric devices. However, relevant experiments showed that a large proportion of photo-generated carriers can escape from MQWs sandwiched in the p-type layer and n-type layer (PIN structure), but not in the NIN structure. In order to study this phenomenon carefully, we applied positive and negative bias to an NIN structure respectively to simulate the PIN structure. By analyzing the photoluminescence (PL) spectra, we observed a weak escape behavior of photon-generated carriers among QWs in NIN structure. The experiment results indicate that strong electric field could drive carriers to escape from QWs rather than relaxation and recombination, while in NIN structure the inhomogeneous distribution of the electric field intensity reduces the carrier transport efficiency. The further study will give new ideas to design and produce photoelectric devices.